The effectiveness of biofilter to reduce the level of nitrate and phosphate content in the butchery liquid waste - Rika Vebriyanti Br Ginting; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The butchery liquid waste is rich in nitrate and phosphate and it need to be processed before being flown to the environment. To understand the effectiveness of combined anaerob-aerob biofilter in reducing the nitrate and phosphate content in the butchery liquid waste, a study was conducted in March – April 2018. The waste (315 L) was treated using a batch system that was consisted of 2 aerob and 2 anaerob tanks. The butchery liquid waste was kept for 10 days in anaerobtanks, 7 days in aerob tanks. By the end of the experiment, the nitrate reduced from 39 mg/l to 12.4 mg/l (the effectiveness was83.21%). While the phosphate reduced from 15.4 mg/l to2.9 mg/l (the effectiveness was 81.16%). Other water quality parameters such as pH was normal and DO was improved (from 1 mg/L to 5 mg/L). The treated waste was used as a mediafor culturingH. pluvialis. Observations of H. pluvialiswere conductedfor 8 days. The H.pluvialis density peaked by the 6th day, it was963,33 cells / ml. Based on data obtained, it can be concluded that the useof anaerob -aerob biofilter was effective forimproving the butchery waste water quality . Keyword : Organic waste, Anaerob tank, Aerob tank, Haemotococcus pluvialis